SITUATIONAL LEADERSHIP AND THE ORGANIZATIONAL LIFE CYCLE: CASE STUDY IN A PATRONAL UNION - Trevisol, Matias; Bencke, Fernando Fantoni; Padilha, Luccas Santin; Roman, Darlan Jose (Revista Gestão Organizacional, 2019)
Studies involving the topics of organizational life cycle and situational leadership institutions in the third sector, as a union, was little explored in the literature. Moreover, recent changes in the Brazilian legislation brought new challenges to these organizations. This study seeks to fill these gaps, to analyze the role of leadership and organizational life cycle in a company union, linking theories against the employers' association. The metaphor of the organizations life cycle allows the analysis of organizations at different stages and, consequently, the role of leadership in the development of courses. The research was qualitative, used methods of case study and oral history, and descriptive and exploratory. Data collection used documental analysis, non-participant observation and in-depth interviews with seven leaders who experienced the historical trajectory of the institution. Among the main contributions of this study, it stands out as a theoretical contribution, the association of situational leadership theories and the organizational life cycle in a union representation institution, still little explored in the literature. Among the practical contributions highlight the situational leadership as alternative for sustainability for organizational cyclic life of a union, which now depend on its resources and internal management capabilities for their survival.